2012
DOI: 10.4236/health.2012.46050
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk of anemia in type-2 diabetic patients in the absence of renal impairment

Abstract: Aim: To determine the incidence of anemia in type-2 diabetic patients with normal renal function and assess the association of other factors related to diabetes with the risk of anemia. Methods: The study group comprised 72 patients with type-2 diabetes. Patients were divided into groups according to glycemic control, gender and age. Serum creatinine, hematocrit, hemoglobin concentration, blood glucose and glycated hemoglobin (HbA1c) of subjects were measured. The presence of anemia was defined by a hemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 15 publications
7
40
4
1
Order By: Relevance
“…Erythropoietin production and release is regulated in part by autonomic nervous system, suggesting that erythropoietin production could be prematurely impaired in patients with poor glycemic control with diabetic autonomic neuropathy. 11 The majority of the study population had macrocytic (40%), while fewer had microcytic (33.8%), normocytic (16.9%) anemia and dimorphic anemia (9.2%).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Erythropoietin production and release is regulated in part by autonomic nervous system, suggesting that erythropoietin production could be prematurely impaired in patients with poor glycemic control with diabetic autonomic neuropathy. 11 The majority of the study population had macrocytic (40%), while fewer had microcytic (33.8%), normocytic (16.9%) anemia and dimorphic anemia (9.2%).…”
Section: Discussionmentioning
confidence: 91%
“…39.4% patients were anemic, among those 80% presented with Normocytic Normochromic, because of the renal involvement. Hematological profile and its significance in T2DM patients were also studied by Thomas SC, 10 Adejumo BI, 11 Bharathi K. 2 In these studies, most of the patients presented with Normocytic and Microcytic anemia, which is due to renal involvement and impaired erythropoietinproduction and release as a result of diabetic autonomic neuropathy. Risk of anemia increases significantly with deterioration of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the incidence of anemic T2DM patients as approximately 15%. Adejumo et al reported the incidence of anemia in T2DM without renal impairment as 15.3% and that poorly controlled diabetes (elevated HbA1c) and old age were correlated with the anemia [16]. Many studies have validated the risk factors for anemia in T2DM without renal impairment.…”
Section: Discussionmentioning
confidence: 97%
“…16 A previous study reported a 15.3% incidence of anemia in participants with diabetes without renal insufficiency. 17 The study added that patients who have poorly controlled diabetes were at greater risk of anemia then those with controlled diabetics. Another study reported that 7.2% of diabetics with normal renal function had anemia.…”
Section: Discussionmentioning
confidence: 99%